2018
DOI: 10.1038/s41598-018-35714-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive hindlimb split-belt treadmill walking in rats by controlling basic muscle activation patterns via phase resetting

Abstract: To investigate the adaptive locomotion mechanism in animals, a split-belt treadmill has been used, which has two parallel belts to produce left–right symmetric and asymmetric environments for walking. Spinal cats walking on the treadmill have suggested the contribution of the spinal cord and associated peripheral nervous system to the adaptive locomotion. Physiological studies have shown that phase resetting of locomotor commands involving a phase shift occurs depending on the types of sensory nerves and stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…The PF layer is thought to determine the spatial motor pattern depending on the phase generated in the RG neurons; that is, it determines the distribution of the co-activated α-motoneurons over time. The muscle synergy hypothesis is one candidate for the determination of the distribution (Ivanenko et al, 2004, 2006) and modeling studies have shown that a motor control system based on this hypothesis could generate locomotion using musculoskeletal models (Aoi et al, 2010, 2013, 2019; Fujiki et al, 2018). In those models, the amplitudes of the α-motoneuron activities were determined in the PF layer.…”
Section: Discussionmentioning
confidence: 99%
“…The PF layer is thought to determine the spatial motor pattern depending on the phase generated in the RG neurons; that is, it determines the distribution of the co-activated α-motoneurons over time. The muscle synergy hypothesis is one candidate for the determination of the distribution (Ivanenko et al, 2004, 2006) and modeling studies have shown that a motor control system based on this hypothesis could generate locomotion using musculoskeletal models (Aoi et al, 2010, 2013, 2019; Fujiki et al, 2018). In those models, the amplitudes of the α-motoneuron activities were determined in the PF layer.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, phase resetting in our model just controlled the timing of the basic signals to determine the motor command using the foot-contact information, which is a very simple strategy. Despite the simple strategy, this timing regulation of the basic signals has been reported to produce various locomotor functions, such as the walk-run transition (Cappellini et al, 2006;Aoi et al, 2019), stepping over an obstacle (Ivanenko et al, 2005;Aoi et al, 2013), and split-belt treadmill walking (MacLellan et al, 2014;Fujiki et al, 2018). Hodgkin-Huxley style neuron model showed that the phase of the neurons' activity rapidly changed by external signals (Rybak et al, 2006a,b), which suggests that FIGURE 5 | PRCs calculated for acceleration and deceleration perturbations for (A) the model without phase resetting, (B) the model with phase resetting, and (C) kinematic measurements of human walking.…”
Section: Contribution Of Phase Resetting Based On Foot Contactmentioning
confidence: 99%
“…It is difficult to fully analyze the locomotor mechanism with animal data alone. Recently, modeling studies have attracted attention because physiological findings and hypotheses can be used to develop reasonably realistic motor control models, and biomechanical and anatomical findings can be used to construct detailed musculoskeletal models (Ivashko et al, 2003;Yakovenko et al, 2004;Ekeberg and Pearson, 2005;Nishii, 2006;Aoi et al, 2013a;Fukuoka et al, 2015;Hunt et al, 2015;Aoi and Funato, 2016;Markin et al, 2016;Fujiki et al, 2018). Motor control and musculoskeletal models are integrated to produce locomotion through forward dynamics simulation.…”
Section: Introductionmentioning
confidence: 99%